Reproducibility of temporally evolving seizure patterns and network connectivity in focal epilepsy - Wei, Yaohong; Zhang, Wei; Liu, Sinclair Xingzhou; Han, Biao; Chen, Qi (Frontiers in Neurology, 2025)
Clinical semiology, waveform patterns, frequency band characteristics, neuronal spiking activity, and connectivity network dynamics exhibit notable reproducibility across seizures in the same patient. However, whether these reproducible features distinctly delineate the epileptogenic zone (EZ), propagation zone (PZ), and non-involved zone (NIZ) and the underlying temporal dynamics remain unclear. In this study, we included 14 patients with focal epilepsy characterized by low-voltage fast activity (LVFA) and with pre-LVFA patterns of rhythmic spikes and/or burst of polyspikes. We examined the reproducibility of raw signals, power spectra, and connectivity patterns across multiple seizures during the interictal, pre-LVFA, and ictal periods. During the ictal phase, raw signals and power spectra in both the high (gamma and ripple) and low (delta) frequency bands demonstrated greater reproducibility in EZ than PZ. Since the high and low frequency bands during seizure onsets have been associated with fast inhibitory interneuron activity and principal neuron activity, respectively, the present results imply that activity of different neuronal populations in the EZ may remain stable across seizures. More importantly, during the pre-LVFA period, the reproducibility of beta band power spectra in EZ, the connectivity patterns within EZ and between EZ and PZ could already discriminate the EZ from the PZ prior to the LVFA onset. Taken together, the reproducibility of raw signals and power spectra in high and low frequency bands during the ictal period could help to improve diagnostic precision of EZ, and the reproducibility of pre-LVFA beta band power spectra, the connectivity within EZ and between EZ and PZ would aid in predicting seizure onsets.